2022
DOI: 10.1029/2022sw003121
|View full text |Cite
|
Sign up to set email alerts
|

Auroral Drivers of Large dB∕dt During Geomagnetic Storms

Abstract: Forecasting geomagnetically induced currents (GICs) remains a difficult challenge, and open questions hindering our understanding include when and where GICs become large and what magnetospheric and ionospheric processes are responsible. This paper addresses these questions by determining the auroral drivers of large dB∕dt (>100 nT/min, a proxy for GICs) on the ground during geomagnetic storms. We study auroras because, although the current system driving dB∕dt is at times challenging to reconstruct, the accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 117 publications
2
15
0
Order By: Relevance
“…Although the importance of the auroral drivers for GMDs suggested by Zou et al (2022) is consistent with this study and our previous studies, we have found that these auroral drivers are not limited to the occurrences of geomagnetic storms. Instead, the most intense nighttime GMDs at high latitudes and extending toward midlatitudes are related statistically to substorms and especially extended periods of magnetotail activity related to high speed streams.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the importance of the auroral drivers for GMDs suggested by Zou et al (2022) is consistent with this study and our previous studies, we have found that these auroral drivers are not limited to the occurrences of geomagnetic storms. Instead, the most intense nighttime GMDs at high latitudes and extending toward midlatitudes are related statistically to substorms and especially extended periods of magnetotail activity related to high speed streams.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study by Zou et al (2022) used coordinated observations from THEMIS and Geophysical Institute Magnetometer Array magnetometers and THEMIS all-sky imagers to statistically examine large dB∕dt intervals during geomagnetic storms from 2015 to 2016. They identified a variety of auroral drivers, including poleward expanding auroral bulges, auroral streamers, poleward boundary intensifications, omega bands, and pulsating auroras.…”
Section: Discussionmentioning
confidence: 99%
“…GIC hazard is determined by a complex interplay between the spectral content of the geomagnetic disturbance, ground conductance, and the orientation and network properties of the affected grid (e.g., Grawe et al., 2018). However, for large statistical surveys of GMD occurrence, 1‐min cadence observations from the SuperMAG network of magnetometers (Gjerloev, 2012) have proved useful (e.g., Rogers et al., 2020; Schillings et al., 2022; Zou et al., 2022). We study sudden changes in those measurements, which for ease of writing we will refer to as “spikes.” Under extreme conditions it is thought that dB / dt can be as large as several 1000s nT min −1 , but even more modest variations of the order of 200 nT min −1 can produce severe GICs (Rodger et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is usually thought that GMDs occur during geomagnetic storms, we find a class of activity that can occur during quiet times.GIC hazard is determined by a complex interplay between the spectral content of the geomagnetic disturbance, ground conductance, and the orientation and network properties of the affected grid (e.g., Grawe et al, 2018). However, for large statistical surveys of GMD occurrence, 1-min cadence observations from the SuperMAG network of magnetometers (Gjerloev, 2012) have proved useful (e.g., Rogers et al, 2020;Schillings et al, 2022;Zou et al, 2022). We study sudden changes in those measurements, which for ease of writing we will refer to as "spikes."…”
mentioning
confidence: 99%
“…This suggests opportunities for research. Even while research is concentrated on nightside ground‐level geomagnetic disturbance that can be generated by substorms (e.g., Engebretson et al., 2020; Vorobev et al., 2019; Zou et al., 2022) and the GICs that they can induce (e.g., Hajra, 2022), the March 1940 storm serves as a reminder of the need for research on “dayside substorms” (e.g., Gromova et al., 2016; Le & Russell, 1993; Tsurutani & Hajra, 2021), which might, themselves, contribute significantly to the induction of GICs, possibly across mid‐latitudes during extremely intense solar‐wind conditions.…”
Section: Local Time Latitude Storm Phasementioning
confidence: 99%